Assessment of Angle of Anterior Chamber with SD-OCT in Patients Presenting to Tertiary Health Care Center: A Cross-sectional Study - Nida Khan; Saroj Gupta; Prakash Agrawal (New Frontiers in Medicine and Medical Research Vol. 5, 2021)
Purpose: To evaluate the normative data of anterior chamber angle in patients presenting to tertiary health care center using anterior segment spectral domain OCT (ASOCT) in central Indian. Design: 120 Consecutive patients presenting to ophthalmology out patient department of tertiary health care center were enrolled in a cross-sectional study. Methods:All patients underwent comprehensive ocular examination. Ocular examination included best corrected visual acuity, refraction, anterior segment examination by slit lamp, fundus examination, gonioscopy by 3 mirror Goldmann contact lens, IOP measured by Goldmann applanation tonometer, OCT analysis of angle of AC .The duration of study was one year six months. This study was approved from the research and ethics committee of the institute. Informed consent was obtained. Data was analyzed by using SPSS 16.0 Results: In our study we have studied the AS-OCT parameters among normal subjects and results of 120 subjects were analyzed. It is noted that mean nasal & temporal AOD was less in females (0.4175 µm, 0.4613 µm) as compared to males (0.4583 µm, 0.4142 µm).This study found that older people had a narrower anterior chamber angle (measured in degrees) and shallower ACD (measured in millimeters). Conclusion: Our study is the first study in central India done with SD-OCT to give normative data of anterior chamber parameters among normal subjects. These normative values will help us identify patients with abnormal values signifying anterior chamber abnormalities.